Avaliação técnica e econômica da colheita de florestas de eucalipto com harvester - Simões, Danilo [UNESP]; Fenner, Paulo Torres [UNESP]; Esperancini, Maura Seiko Tsutsui [UNESP] (My University, 2010)
The acquisition of machinery used in timber harvesting depends on high financial investment, which implies the need for assessments that allow defining more precisely, what is the machine or the whole more recommended for streamlining the operation. This study aimed to technically and economically evaluating the performance of a harvester in Eucalyptus forest harvest first cut. The technique analysis included a time and movements, productivity, efficiency operational and mechanical availability. The economic analysis included the parameters operational cost, harvesting cost and energy consumption. The results obtained from the technological-economic parameters evidenced that of Diameter at Breast Height directly influenced the productivity of harvester. Consequently the lower costs of forest harvest were obtained for the compartments with wider diameter trees.

A aquisição de máquinas empregadas na colheita florestal depende de alto investimento financeiro, o que implica na necessidade de avaliações que possibilitem definir com maior precisão, qual será a máquina ou o conjunto mais preconizado para a racionalização dessa operação. O objetivo deste estudo foi avaliar técnica e economicamente o desempenho de um harvester em colheita florestal de eucalipto em primeiro corte. A análise técnica englobou um estudo de tempos e movimentos, produtividade, eficiência operacional e disponibilidade mecânica. A análise econômica englobou os parâmetros do custo operacional, custo de colheita florestal e rendimento energético. Os resultados dos parâmetros técnico-econômicos evidenciaram que o Diâmetro à Altura do Peito influenciou diretamente a produtividade do harvester. Consequentemente os menores custos de colheita florestal foram obtidos para as parcelas experimentais com árvores de maior diâmetro.
Technical and economical evaluation of the Eucalyptus forest harvest with harvester
Keywords: Performance evaluation; Energy consumption; Time and movements; Avaliação de desempenho; Rendimento energético; Tempos e movimentos